Pengaruh Harga dan Kualitas Terhadap Keputusan Pembelian Rokok Signature Kretek - Muhammad Suryo Wandhito Putra Sunarto; Aditya Liliyan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of price and product quality on purchasing decisions of Gudang Garam Signature Kretek cigarettes in the premium machine-made kretek segment. The Indonesian tobacco industry continues to face sustained regulatory pressure through excise tax increases and intensifying brand competition, prompting consumers to reassess purchasing decisions using both rational evaluation and experiential judgment. A quantitative correlational approach was employed in this study. Primary data were collected through structured Likert-scale questionnaires distributed to 100 active consumers of Gudang Garam Signature Kretek selected using purposive sampling techniques. Data analysis was conducted through validity testing, reliability testing, and multiple linear regression analysis using SPSS software. The results indicate that price and product quality have a positive and significant influence on purchasing decisions, both partially and simultaneously. Product quality emerged as the most dominant factor, suggesting that premium cigarette consumers prioritize consistent quality, taste, aroma, and overall consumption experience as the primary basis for decision-making. Meanwhile, price remains an important rational reference for assessing the fairness between perceived benefits and financial sacrifice. Simultaneously, both variables explain 50 percent of the variation in purchasing decisions, while the remaining variance is influenced by other factors outside the research model. These findings highlight that purchasing decisions in the premium cigarette market are shaped by a value-based assessment, where sustained product quality and adaptive pricing strategies play a critical role in maintaining consumer loyalty amid regulatory pressure and evolving market dynamics